Serum Creatinine and Cystatin-C Levels in Patients Diagnosed with Kidney Disorders - Nurmeily Rachmawati; Yuliani Yuliani; Citra Trisna; Syarah Anliza; Ahmad Yani (Journal of Noncommunicable Diseases Prevention and Control, 2023)
The development of non-communicable diseases still dominates in Indonesia. One of them is kidney failure, which contributes to the burden of disease in the world with a fairly high death rate. Examination parameters to indicate renal condition can be seen from several laboratory examination results, such as levels of creatinine, urea, cystatin-C, uric acid, microalbuminuria, and others. The aim of this study is to obtain a brief overview of creatinine and cystatin-C levels in patients diagnosed with kidney disorders to determine the extent of the severity of the disease that has occurred. The method used in this research is descriptive analysis with laboratory examination using a cross-sectional approach. The number of samples in this research was 30. Based on the research results, respondents were dominated by women (53.3%) with an age range of 28–76 years. The proportion of respondents' creatinine levels was still more in the normal category, and the proportion exceeding the normal limit for male and female respondent groups was the same, namely 50% each. Meanwhile, the cystatin-C levels of respondents were more often found in the above-normal category (63.3%), which was dominated by the group of female respondents (57.9%).